2012
DOI: 10.3109/13668250.2012.736614
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of mothers of children with autism: Managing multiple roles

Abstract: The findings indicate that health professionals working with these families must support mothers in managing various aspects of their lives, including those not directly related to their child with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 34 publications
4
112
0
5
Order By: Relevance
“…‘… it's impossible to maintain your role in other areas because there's only one you and there's only 24 hours in a day and so everything else has to give a bit’ (Safe et al . , p. 299)…”
Section: Resultsmentioning
confidence: 98%
“…‘… it's impossible to maintain your role in other areas because there's only one you and there's only 24 hours in a day and so everything else has to give a bit’ (Safe et al . , p. 299)…”
Section: Resultsmentioning
confidence: 98%
“…There is little research, most of it qualitative, that seeks to explore the broader parent perspective and evolving life experience of what it is like to raise a child with ASD (Corcoran et al, 2015; Hoogsteen and Woodgate, 2013; King et al, 2006; Safe et al, 2012). Rutter (2007) pointed out that when studying parental reactions to adversity, it is important to consider the life span perspective in addition to past and present mental operations, and individual traits and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that have aimed for richness in narrative, such as, the studies by Reitmanova and Gustafson (2008) and Safe et al (2012), have also reported findings with saturation and variability with this number of research participants. Hence, we commenced with this number as an initial target, and if saturation was not met, we planned to recruit additional participants.…”
Section: Research Participantsmentioning
confidence: 83%